Think Logically not mathematically [part-32]

Algebra Level 4

( a 3 + a 2 + a ) + ( b 3 + b 2 + b ) + ( c 3 + c 2 + c ) (a^3+a^2+a)+(b^3+b^2+b)+(c^3+c^2+c)

If a a , b b , and c c are the roots of the equation x 3 + 2 x = 1 x^3+2x=1 , then find the value of the expression above.


The answer is -1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Jun 26, 2016

X = a 3 + a 2 + a + b 3 + b 2 + b + c 3 + c 2 + c Note: 1 = 1 2 a + a 2 + a + 1 2 b + b 2 + b + 1 2 c + c 2 + c = 3 ( a + b + c ) + a 2 + b 2 + c 2 Note: 2 = 3 ( 0 ) + ( a + b + c ) 2 2 ( a b + b c + c a ) Note: 2 = 3 + ( 0 ) 2 2 ( 2 ) = 1 \begin{aligned} X & = \color{#3D99F6}{a^3}+a^2+a + \color{#3D99F6}{b^3}+b^2+b + \color{#3D99F6}{c^3}+c^2+c \quad \quad \small \color{#3D99F6}{\text{Note: 1}} \\ & = \color{#3D99F6}{1-2a}+a^2+a + \color{#3D99F6}{1-2b}+b^2+b + \color{#3D99F6}{1-2c}+c^2+c \\ & = 3-(\color{#3D99F6}{a+b+c})+\color{#D61F06}{a^2+b^2+c^2} \quad \quad \small \color{#3D99F6}{\text{Note: 2}} \\ & = 3-(\color{#3D99F6}{0})+\color{#D61F06}{(a+b+c)^2-2(ab+bc+ca)} \quad \quad \small \color{#D61F06}{\text{Note: 2}} \\ & = 3+\color{#D61F06}{(0)^2-2(2)} \\ & = \boxed{-1} \end{aligned}


Notes:

  1. Since a a , b b and c c are roots of x 3 + 2 x = 1 x^3 +2x = 1 or x 3 = 1 2 x x^3 = 1 - 2x { a 3 = 1 2 a b 3 = 1 2 b c 3 = 1 2 c \implies \begin{cases} a^3 = 1-2a \\ b^3 = 1-2b \\ c^3 = 1-2c \end{cases}

  2. Vieta's formulas: { a + b + c = 0 a b + b c + c a = 2 \begin{cases} a+b+c = 0 \\ ab+bc+ca = 2 \end{cases}

Perfect! I did the same. :)

Lucas Nascimento - 4 years, 11 months ago

By Vieta's formulas: { a + b + c = 0 a b + a c + b c = 2 a b c = 1 \begin{cases}a+b+c=0\\ab+ac+bc=2\\abc=1\end{cases}

Therefore, a 3 + a 2 + a + b 3 + b 2 + b + c 3 + c 2 + c = a 3 + b 3 + c 3 + a 2 + b 2 + c 2 + a + b + c = 3 a b c + ( a + b + c ) ( ( a + b + c ) 2 3 a b 3 a c 3 b c ) + ( a + b + c ) 2 2 a b 2 a c 2 b c + a + b + c = 3 4 = 1 a^3+a^2+a+b^3+b^2+b+c^3+c^2+c\\=a^3+b^3+c^3+a^2+b^2+c^2+a+b+c\\=3abc+(a+b+c)((a+b+c)^2-3ab-3ac-3bc)+(a+b+c)^2-2ab-2ac-2bc+a+b+c\\=3-4\\=-1

Sudoku Subbu
Jun 25, 2016

Given, a, b, c are the roots of the equation x 3 + 2 x 1 = 0 x^3+2x-1=0 = > a + b + c = 0 => a+b+c=0 a b + b c + c a = 2 ab+bc+ca=2 a b c = 1 abc=1 and also a 2 + b 2 + c 2 = ( a + b + c ) 2 2 ( a b + b c + c a ) a^2+b^2+c^2=(a+b+c)^2-2(ab+bc+ca) = > a 2 + b 2 + c 2 = 0 ( 2 × 2 ) = 4 => a^2+b^2+c^2=0-(2\times2)=-4 here, a + b + c = 0 = > a 3 + b 3 + c 3 = 3 a b c = 3 × 1 = 3 a+b+c=0\space\space\space => a^3+b^3+c^3=3abc=3\times1=3\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space Therefore, ( a 3 + a 2 + a ) + ( b 3 + b 2 + b ) + ( c 3 + c 2 + c ) = ( a 3 + b 3 + c 3 ) + ( a 2 + b 2 + c 2 ) + ( a + b + c ) (a^3+a^2+a)+(b^3+b^2+b)+(c^3+c^2+c)\space=\space(a^3+b^3+c^3)+(a^2+b^2+c^2)+(a+b+c) = 3 4 + 0 =3-4+0 = 1 =-1

Typo: a 3 + b 3 + c 3 = 3 a b c = 3 × 1 = 3 a^3+b^3+c^3=3abc=\color{#3D99F6}{3} \times 1 = 3

Hung Woei Neoh - 4 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...